Atypical presentation of rheumatic fever - Yewale, Sushil; Lahiri, Keya; Najmuddin, Fehmida; Sude, Anand (Indian Journal of Case Reports, 2021)
Sydenham Chorea (St. Vitus dance) occurs in about 10-15% of children with acute rheumatic fever. Herein, we present the case of a 5-year-old male child with hemichorea and arthralgia. The child also presented with mild mitral regurgitation and mild aortic regurgitation. Appropriate management is essential to prevent mortality, morbidity, and psychosocial disability in such cases. We would also like to shed light on the challenges faced in the management of chorea in young children with key emphasis on the anticipation of adverse reactions to commonly used medications.